The Impact of TikTok Social Media on Users: A Neuropsychological Perspective - Thomas Ari Wicaksono; Viki Love Reformasianto; Diffani Mufidah; Elsa Anggelina; Supra Wimbarti; Sri Kusrohmaniah (Psikostudia : Jurnal Psikologi, 2024)
TikTok has a personalized algorithm and is designed with a user-centered approach, which raises concerns about the impact it will have on cognitive function and user behavior. There is a lack of literature that discusses the integration of topics between the impact of TikTok algorithms on cognitive function and user behavior. This study uses the literature review method by collecting and selecting relevant literature from various databases to compile information about the impact of using TikTok on cognitive function and individual behavior in one scientific article. Based on the results of a review of 14 literatures, TikTok has a negative impact on several areas in the brain. The areas affected by using Tiktok are the user's reward system, activation of the default mode network (DMN) and ventral tegmental area (VTA), decreased gray matter volume (GMV) in the amygdala, and affect the hippocampus. Then, the impact of Tiktok on individual behavior includes decreased concentration, impulsivity in making decisions, and addictive behavior. Therefore, the use of TikTok needs to be balanced with awareness of the potential impact behind it and wise choices for its use.TikTok memiliki Algoritma yang dipersonalisasi dan dirancang dengan pendekatan yang berpusat pada pengguna atau user-centered, hal ini menimbulkan kekhawatiran pada dampak yang akan dihasilkan pada fungsi kognitif dan perilaku pengguna. Kurangnya literatur yang membahas mengenai integrasi topik antara dampak algoritma Tiktok pada fungsi kognitif dan perilaku pengguna. Studi ini menggunakan metode literature review dilakukan dengan mengumpulkan dan menyeleksi literatur yang relevan dari berbagai database untuk menghimpun informasi mengenai dampak penggunaan Tiktok pada fungsi kognitif dan perilaku individu dalam satu artikel ilmiah. Berdasarkan hasil tinjauan dari 14 literatur, Tiktok memberi dampak negatif terhadap beberapa area di otak. Area yang terdampak dari penggunaan Tiktok yaitu reward system pengguna, aktivasi area default mode network (DMN) dan ventral tegmental area (VTA), penurunan grey matter volume (GMV) pada amygdala, dan mempengaruhi hippocampus. Kemudian, dampak Tiktok terhadap perilaku individu di antaranya menurunnya konsentrasi, impulsif dalam mengambil keputusan, dan perilaku adiktif. Karenanya, penggunaan Tiktok perlu diimbangin dengan kesadaran akan dampak potensial dibaliknya serta pilihan-pilihan bijak untuk penggunaannya.